2021
DOI: 10.1186/s13071-020-04555-8
|View full text |Cite
|
Sign up to set email alerts
|

An atlas of tsetse and animal African trypanosomiasis in Zimbabwe

Abstract: Background In the 1980s and 1990s, great strides were taken towards the elimination of tsetse and animal African trypanosomiasis (AAT) in Zimbabwe. However, advances in recent years have been limited. Previously freed areas have been at risk of reinvasion, and the disease in tsetse-infested areas remains a constraint to food security. As part of ongoing control activities, monitoring of tsetse and AAT is performed regularly in the main areas at risk. However, a centralized digital archive is mi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
18
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
6
1
1

Relationship

1
7

Authors

Journals

citations
Cited by 19 publications
(19 citation statements)
references
References 33 publications
1
18
0
Order By: Relevance
“…The methodology to develop the atlas of tsetse and AAT in Burkina Faso is broadly based on the FAO continental atlas [16][17][18], and a similar approach has already been used at the national level in Sudan [19], Mali [20], Kenya [21] and Zimbabwe [22]. The main difference between the continental and the national atlases is that the former is solely based on publicly available data from peer-reviewed journals, while the latter include all published or unpublished data collected in a given country.…”
Section: Methodsmentioning
confidence: 99%
“…The methodology to develop the atlas of tsetse and AAT in Burkina Faso is broadly based on the FAO continental atlas [16][17][18], and a similar approach has already been used at the national level in Sudan [19], Mali [20], Kenya [21] and Zimbabwe [22]. The main difference between the continental and the national atlases is that the former is solely based on publicly available data from peer-reviewed journals, while the latter include all published or unpublished data collected in a given country.…”
Section: Methodsmentioning
confidence: 99%
“…Three clinical trial studies showed that the efficacy of NECT is non-inferior to standard eflornithine monotherapy [ 3 , 5 , 7 ]. In the clinical trial by Schmid et al, the primary outcome was the proportion of patients discharged alive from the hospital [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
“…Three clinical trials defined cure rate as the absence of trypanosomes in the body fluids and leucocyte count less than 20 cells per μL 18 months after treatment [ 3 , 5 , 7 ]. While the study by Schmid et al, the primary outcome was the proportion of patients discharged from the hospital [ 12 ].…”
Section: Reviewmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, T. brucei has been verified as a valid model system for T. cruzi , for compounds targeting the PEX14 and PEX5 interaction ( Dawidowski et al, 2017 ). Last but not the least, animal infections of livestock (nagana) caused by T. congolense , T. vivax , and T. brucei species, leading to the annual loss of over 4 billion United States dollars are remaining great challenges ( Shereni et al, 2021 ). This demonstrates the importance of using T. brucei as the model organism for drug development.…”
Section: Introductionmentioning
confidence: 99%